2013
DOI: 10.1371/journal.pone.0078231
|View full text |Cite
|
Sign up to set email alerts
|

Nicorandil in Patients with Acute Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention: A Systematic Review and Meta-Analysis

Abstract: BackgroundNicorandil, as an adjunctive therapy with primary percutaneous coronary intervention (PCI), had controversial benefits in cardioprotection in patients with acute myocardial infarction (AMI).Methods and ResultsWe performed a systematic review of randomized controlled trials (RCTs) comparing treatment with nicorandil prior to reperfusion therapy with control (placebo or no nicorandil) in patients who suffered from AMI and performed primary PCI. PubMed, EMBASE and CENTRAL databases and other sources wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 36 publications
4
18
0
Order By: Relevance
“…The present results also expand on those of a prior metaanalysis of clinical trials evaluating the outcomes of nicorandil at the time of reperfusion therapy in patients with acute MI undergoing PCI [38]. The authors of that report found that administration of nicorandil at the time of reperfusion was associated with improved coronary reflow, suppression of ventricular arrhythmia, and improved left ventricular ejection fraction.…”
Section: Discussionsupporting
confidence: 76%
“…The present results also expand on those of a prior metaanalysis of clinical trials evaluating the outcomes of nicorandil at the time of reperfusion therapy in patients with acute MI undergoing PCI [38]. The authors of that report found that administration of nicorandil at the time of reperfusion was associated with improved coronary reflow, suppression of ventricular arrhythmia, and improved left ventricular ejection fraction.…”
Section: Discussionsupporting
confidence: 76%
“…Nicorandil, a NO-donor and KATP channel opener, has been shown to reduce the infarct size in rabbit hearts (Argaud et al, 2009). However, a meta-analysis of available small-scale clinical trials could not show direct benefit in myocardial infarction patients from nicorandil treatment, possibly due to the lack of large clinical trials (Wu et al, 2013).There are several novel compounds with potential cardioprotective properties, whose mechanisms of action depend upon NO signalling. PostC with isoflurane decreases infarct size in wild-type mice.…”
mentioning
confidence: 99%
“…Some patients experienced transient hypotension for a short time, but prolonged hypotension was not noted, and the use of vasopressor or intra‐aortic balloon pump (IABP) during the procedure was also similar in both groups . Compared with drugs such as adenosine, verapamil, and nicorandil that have not yet been proved to be associated with conclusive improvements in clinical outcome, NTP would be a more promising adjuvant drug in the treatment of NR, and the possible mechanisms partly due to intracoronary NTP could produce an equivalent but more prolonged coronary hyperemia than adenosine or other drugs . There are also some limitations in the present study.…”
Section: Discussionmentioning
confidence: 99%